Filipino female police officers investigating women and children cases: Secondary traumatic stress, burnout, and coping strategies - Alagos, Jacquiline Noche (Animo Repository, 2022)
Indirect exposure to trauma of the helping profession is often overlooked in most literature. This study examines the secondary traumatic stress and burnout of Filipino female police officers handling women and children cases and its influence on their coping strategies. In this context, secondary traumatic stress is defined using Figley’s (1995) definition of STS𑁋the natural consequent behaviors and emotions resulting from knowing about a traumatizing event experienced by a significant other—the stress resulting from helping or wanting to help a traumatized or suffering person. To investigate the secondary traumatic stress and burnout of Filipino female police officers handling women and children cases and its influence on coping strategies, a semi-structured interview along with a symptoms checklist was conducted with 9 participants. The data from the interviews were analyzed using thematic analysis. The results showed the emergence of seventeen themes. Under STS: highly sensitive with clients’ experiences, fear, anxiety, intrusive thoughts, heightened awareness, sleeplessness. Under burnout: exhaustion, anger and irritability at home or at work, demotivation, susceptibility to physical illness or problems. Under coping strategies: seeking social support, balancing professional and social life, finding positivity at work, self-efficacy, smoking and alcohol consumption, stress eating, and self-efficacy. These results suggest that constant exposure to traumatized populations can prompt STS development and burnout, but several coping strategies can help alleviate its possible development. Keywords: secondary traumatic stress, burnout, coping strategies